IDENTIFICATION OF WATER MASSES AND CURRENT PATTERNS IN THE NORTHWESTERN SUMATRA WATERS DURING THE ONSET OF THE WEST MONSOON 2017 - Damayanti, Agustina
The northwest waters of Sumatra, directly adjoining the Indian Ocean, cause the water masses and current patterns to be influenced by the dynamics of the Indian Ocean. The northwest waters of Sumatra has an interesting conditions, which has a large range of Oxygen Minimum Zones (OMZs) depths with dissolved oxygen concentrations of 30-35 ?mol/Kg at depths of 140-1200 m. This applies as usual to conditions of waters in the open ocean. This study identifies the water masses using the T-S diagram, T-O diagram, S-O diagram, and Optimum Multiparameter (OMP) analysis, as well as knowing the patterns of ocean currents in the northwestern waters of Sumatra during the onset of the west monsoon 2017. The main data used are CTD and ADCP from Widya Nusantara Expedition conducted on December 3- 8, 2017. From the T-S diagram analysis, seven water masses were identified that compose the northwest waters of Sumatra, namely Bay of Bengal Water (BBW), Subtropical Lower Water (SLW), Indian Equatorial Water (IEW), Red Sea-Persian Gulf Intermediate Water (RSPGIW), North Indian Deep Water (NIDW), North Atlantic Deep Water (NADW), and Circumpolar Deep Water (CDW), and from the T-O diagram the ASW was identified. From the OMP calculation results, BBW dominates the northwest waters of Sumatra at a depth of 50-150 m with a contribution of 55-60%. At this depth, BBW is mixed with ASW which has a contribution of 15-40%. At a depth of 140-1600 m, IEW is identified with a contribution of 5-20%. IEW is mixed with RSPGIW which identified at a depth of 160-2000 m with a contribution of 20-90%. At a depth of >900 m, NIDW is identified with a contribution of 5-95%. The distribution of water masses contribution in each transect is influenced by ocean current conditions. In the northwest waters of Sumatra, the current at a depth of 15 m moves northwest with a speed of up to 1.5 m/s. As depth increases, there is a change in current direction due to the deflection of the Coriolis force. At a depth of 50-75 m, the current moves north-northeast with a speed of up to 1 m/s, then at a depth of 100 m, the current moves northeast with a speed of 0.8 m/s. At a depth of 200-500 m, the current direction looks irregular with a speed of 0.5-0.6 m/s.